International students’ transition to university: Connection and disconnection in online group work interactions - Jade Sleeman; Catherine Lang; Eva Dakich (Student Success)
An Australian higher education experience often includes group work as an important social learning opportunity. For international students, taking part in a group assignment can positively influence learning and adjustment to the new cultural and educational context through social interaction. However, students are increasingly choosing to use digital technologies to participate in group assignments, which may impact on opportunities available to make social connections with peers. This study investigated the experiences of 26 international students as they transitioned to study at an Australian university about their use of social media for group assignments and their resulting perceptions of connection to classmates. Analysis of the results suggests that students who engaged in collaborative rather than cooperative interactions via social media were more likely to perceive a connection to their classmates. This has implications for educators to include classroom modelling of digitally-mediated collaborative interactions to benefit students’ participation in group assignments, which can improve the transition experience through social connection.